Urban flooding and ground‐related homes in Canada: an overview. Issue 3 (27th July 2015) - Sandink, D.
Abstract: Urban flooding associated with extreme precipitation is a significant cause of disaster damages for municipalities, homeowners and insurers in Canada. Several approaches have been applied to reduce urban flood risk at the municipal and homeowner scales, including addressing inflow/infiltration in wastewater systems, accommodating extreme stormwater flows in subdivision design and protecting individual homes from flooding. Insurers have also engaged in managing urban flood risk through interactions with individual policyholders and initiatives aimed at better understanding urban flood risk and risk mitigation options. Requiring mitigation measures at the time of the construction of homes, improving insurance data, application of incentives for appropriate private side retrofits, and improved collaboration between insurers and municipalities for identification of urban flood risk areas provide additional opportunities for urban flood risk reduction. Further, senior levels of governments should support inflow/infiltration reduction and application of climate change information to improve the planning and design of municipal infrastructure.